Literature Review: mengenai Stigma atau Pandangan Sosial Terhadap Anak dengan Hambatan Intelektual - Azizah, Khalda; Zahra, Anna Hamidah; Alifa, Seva Yasmin; Ainurrohmah, Kayla; Sura Mangu, Maria Kolenstika; Maulidina, Citra Ashri (Universitas Negeri Jakarta, 2025)
Children with intellectual disabilities often experience unfair treatment due to the social stigma imposed on them by society. Society often gives negative labels such as